2006
DOI: 10.2215/cjn.01191005
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Referral for Renal Transplant Evaluation in Recipients of Nonrenal Solid-Organ Transplants

Abstract: The use of cyclosporine and tacrolimus therapy in nonrenal (heart, heart/lung, lung, and liver) transplantation has resulted in improved patient and graft survival. Nephrotoxicity is one of the major side effects of tacrolimus and cyclosporine therapy and may lead to ESRD. The trend of referral of nonrenal solid-organ transplant recipients for kidney transplant evaluation at a large multiorgan transplant center was examined. Records of all patients who were referred for renal transplantation at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Likewise, a Canadian registry study found significantly decreased survival in post-OLT patients who underwent RRT compared with matched nontransplant chronic dialysis control patients, with 5-year patient survival rates of 17% and 43% for the post-OLT patients and controls, respectively (p = 0.01) [23]. Thus, given the increasing frequency of renal transplant referrals for recipients of nonrenal solid-organ transplants [24], two decisions must be made: the appropriate time to list OLT patients undergoing RRT for a subsequent kidney transplant and whether they should be prioritized for kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a Canadian registry study found significantly decreased survival in post-OLT patients who underwent RRT compared with matched nontransplant chronic dialysis control patients, with 5-year patient survival rates of 17% and 43% for the post-OLT patients and controls, respectively (p = 0.01) [23]. Thus, given the increasing frequency of renal transplant referrals for recipients of nonrenal solid-organ transplants [24], two decisions must be made: the appropriate time to list OLT patients undergoing RRT for a subsequent kidney transplant and whether they should be prioritized for kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…7 It can also progress to require dialysis and/or kidney transplantation. 13 Most importantly, a posttransplant diagnosis of end-stage chronic renal failure has been shown to be associated with reduced survival. 2,8 To our knowledge, no previous studies have looked at the incidence or predictors of posttransplantation renal dysfunction in the CF population.…”
Section: Cohort Selectionmentioning
confidence: 99%
“…It is not uncommon that renal failure complicates nonrenal solid‐organ transplantation, leading to a kidney transplant . Improvements in medical care are allowing patients with prior nonrenal solid‐organ transplantation to live longer and to eventually become candidates for kidney transplantation . Renal transplantation after prior nonrenal solid‐organ transplantation has increased over the last 2‐3 decades.…”
Section: Introductionmentioning
confidence: 99%